CONSIDERATIONS FOR THE PROCESS OF TEACHER TRAINING ABROAD (EDUCATION IN THE 21ST CENTURY, 2023)
The features of continuous education of teachers in developed countries is analyzed in the article, discovering the main problems of teacher retraining in the world, and stating the content and forms of work.     There are a number of organizational and substantive differences in the teacher retraining systems of different countries, which will provide an opportunity for essentially improving the teacher retraining system in the Republic of Armenia. The analysis of foreign experience organization of retraining allows us to conclude that there are many concepts and ideas that are carried out in practice, many of which can be applied in the retraining system of our country.    An important feature of retraining in developed countries today is that in the conditions of the market economy, the teacher shares the responsibility of increasing professionalism with the state. The content of teacher retraining programs in developed countries is multifaceted and extensive. It has been confirmed that the study of information technology arouses the greatest interest among teachers.    The research was based on V. B. Garga, T. V. Tsirlina, O. N. Orlova, M. Böhmer and research by other authors, whose valuable analyzes shed light on the main features of the teacher retraining system in the world.    By summarizing the analysis of the practice of retraining abroad, we underline some features that are also of interest to Armenian education, strengthening the professional development of teachers according to their needs and program development based at the school; active interaction of schools with universities and other institutions, the support of state and public bodies and university specialists to teachers, the variety of forms of retraining, providing organizational support to teachers and distance learning as an alternative means of teacher retraining.    In general, the problem of teacher retraining is actual and relevant for most countries., On one hand the professional demands and needs of the teacher, on the other hand and the demands of society's development match and coincide during such retraining.    In developed countries, the state gives the teacher the opportunity to update his knowledge and skills, and it corresponds to the interests of both- the teacher and his students, the school and the state in general.    At the same time, teachers in these countries also share with the state the responsibility for own professional development.
Keywords: Retraining; improvement of qualification; professional development of teachers; retraining and continuous education system model of teacher